FABRIKASI DAN SIFAT-SIFAT MEKANIS KOMPOSIT BERBAHAN CANGKANG BIJI KARET (HEVEA BRASILIENSIS) - Restu Budianto; Andi Idhil (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Rubber is one of the most abundant natural resources in Indonesia. Indonesia is the country with the second-largest rubber production in the world. Based on data from the Ministry of Agriculture, the area of national rubber plantations reaches an area of 3.67 Ha. Rubber seed has a shell that has not been utilized optimally; it is only burnt and not utilized. Utilizing the seed shell material rubber as a reinforcing material is expected to increase efficiency and economic value. This research was carried out by doing variations in the volume filler fraction with a polyester matrix of 20%, 30%, and 40% with the hand lay-up method. The variations applied were tested using tensile, bending and water absorption. The highest tensile strength results is obtained at a variation of 20% with a value of 15.38 MPa. The highest bending strength is obtained on the variation of 20% with a value of 181.15 MPa. The optimum water absorption value is obtained at a variation of 20% with a value of 0.53%.